Dampak Covid -19 Terhadap Pendapatan Pedagang Pasar di Desa Tinading Kecamatan Lampasio Kabupaten Tolitoli - Yuliana (Formosa Journal of Sustainable Research, 2022)
This study aims to determine the impact of the Covid-19 pandemic on the income of market traders in Tinading Village, Lampasio District, Tolitoli Regency. The method used is descriptive analysis of qualitative methods using saturated sampling where all traders who exist/or live in the market are used as research samples. The primary data used are the results of direct observations and interviews with market traders and officials from the Village of Tinading, Lampasio District, Tolitoli Regency, Central Sulawesi Province, regarding the income earned by market traders before the pandemic, during the pandemic, and after the pandemic. From the results of interviews that the income of market traders has decreased significantly reaching more than 50% during the pandemic due to the PSBB so that the working hours / market operations are limited which causes the market to be quiet and causes goods to sell less so that the income of market traders is reduced. But after going through the pandemic period the income of market traders began to gradually improve.